Trabajo decente: una categoría política y técnica para el análisis y medición de las condiciones de trabajo en Colombia - Correa Montoya, Guillermo (Revista Controversia, 2010)
Este artículo explora algunas de las discusiones actuales frente a la categoría de trabajo decente, ubicando sus horizontes interpretativos como concepto de integración de las apuestas centrales de la OIT y como categoría en construcción que configura el piso de los derechos en el mundo laboral contemporáneo. A partir de esta revisión teórica se señala una propuesta que puede asumirse como concepto teórico-político y técnico. En esta dirección se establece una mirada analítica frente a las principales propuestas y estrategias para la identificación y medición de indicadores específicos para el contexto colombiano apoyado fundamentalmente en fuentes de información oficial referidas al mercado de trabajo. Palabras Clave: Trabajo decente, Indicadores, Trabajadores, OIT, Seguridad, Colombia ABSTRACT DECENT WORK: A POLITICAL AND TECHNICAL CATEGORY FOR THE ANALYSIS AND MEASUREMENT OF WORKING CONDITIONS IN COLOMBIA Abstract This article explores some of the actual dimensions of the concept of Decent Work, locating its interpretative horizons as a concept that integrates the central objectives of the ILO, as well as a category in construction that sets a baseline for rights in today’s world of work. Out of this theoretical revision, the autors signal a proposal that could encompass a theoretical, political and technical concept and along these lines, an analytical perspective is established as a means of offering a critique of the principal proposals and strategies used for the identification and measurement of Decent Work. This careful examination and summary of the state-of-art concerning this topic, leads the authors towards an alternative way of specifying indicators of decent work for the Colombian context, which is supported, primarily, on official information sources refering to the country’s labor market. Key Words: Decent Work, Indicators, Workers, ILO, Social Security, Colombia